IMPLEMENTASI SUPERVISI AKADEMIK UNTUK MENINGKATKAN KETERAMPILAN GURU DALAM MELAKSANAKAN PROGRAM BELAJAR DARI RUMAH (BDR) SELAMA MASA PANDEMI COVID - 19 - Agung Riyanta (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aims to determine whether the Implementation of Academic Supervision to Improve Teacher Skills in Implementing Home Learning Programs (BDR) During the Covid-19 Pandemic Period at SMA Negeri 1 Kubu, Rokan Hilir Regency. Based on the description of the background, problem identification and problem limitation, the focus of this research relates to the Implementation of Academic Supervision to Improve Teacher Skills in Implementing Home Learning Programs (BDR) During the Covid-19 Pandemic Period at SMA Negeri 1 Kubu, Rokan Hilir Regency. This School Action Research was carried out only in SMA Negeri 1 Kubu, Rokan Hilir Regency. Under the supervision of the researchers themselves. This was chosen because it really supports the task of school supervisors to determine the implementation of the Learning from Home Program (BDR) during the Covid-19 Pandemic. This research was carried out in two cycles. The duration of this research is approximately 1 month. The population in this study were all teachers in SMA Negeri 1 Kubu, Rokan Hilir Regency who were in the area under the guidance of the researcher as the principal of the school, amounting to 37 people. From the description of data processing and discussion, it was concluded that the pedagogic competence of teachers was obtained in the first cycle by 57% in the good category and in the second cycle increased to 88% in the good category. This means that the Implementation of Academic Supervision to Improve Teacher Skills in Implementing Home Learning Programs (BDR) During the Covid-19 Pandemic Period at SMA Negeri 1 Kubu, Rokan Hilir Regency is said to be successful.